Toleration and reciprocity: commentary on Martha Nussbaum and Henry Shue - Michael Blake (Politics Philosophy Economics 2002; 1; 325, 2002)
Rawls's Law of Peoples has not gathered a great deal of public support. The reason for this, I suggest, is that it ignores the differences between the international and domestic realms as regards the methodology of reciprocal agreement. In the domestic realm, reciprocity produces both stability and respect for individual moral agency. In the international realm, we must choose between these two values - seeking stable Relations between states, or respect for individual moral agency. Rawls's Law of Peoples ignores the stark nature of this choice by insisting that the only legitimate extension of liberal toleration abroad is the toleration of different forms of political organization. It is this attempt to overcome liberalism's tragic dilemma which, I suggest, has made Rawls's international theory less attractive than his domestic theory. I also suggest that this difficulty is at the base of the further difficulties identified by Henry Shue and Martha Nussbaum in their accompanying essays.